The smallest marine bivalves from the end of the world (Tierra del Fuego, Isla de Los Estados and Burdwood Bank) - Güller, Marina; Zelaya, Diego Gabriel (Polar Biology)
Small molluscs are known to be particularly abundant towards the poles. Although recent studies on sub-Antarctic waters of the southernmost tip of South America have begun to show a highly diversified small-sized fauna, micromolluscs have not yet received sufficient attention. Recently, samplings targeting the smallest molluscan benthic fauna have been conducted in the sub-Antarctic waters of South America, providing material of three new minute species occurring in The End of the World (Tierra del Fuego, Isla de los Estados and Burdwood Bank). The present study describes Pachykellya fuegiensis n.sp. (Neoleptonidae), Benthocardiella ituartei n.sp. and Benthocardiella finisterra n.sp. (Condylocardiidae). These are not only the smallest bivalves currently known from the area, but are also smaller than any other species thus far known from the adjacent Antarctic waters, and are included among the smallest species of their respective genera. To confirm generic placement, the type species of Pachykellya (P. edwardsi F.B. Bernard 1897) and Benthocardiella (B. pusilla Powell 1930) are studied for the first time with scanning electron microscopy. This study allows to amend the previous descriptions of hinge teeth number, morphology and arrangement for these genera. Based on these new findings, Pachykellya and Benthocardiella are here reported for the first time in South America. Fil: Güller, Marina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Zelaya, Diego Gabriel. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina